"OK Boomer": Demagogic Discourse and Intergenerational Communication. Issue 2 (3rd April 2023) - Anderson, Lindsey B.
ABSTRACT: "OK boomer, " is a viral phrase used by members of Generation Z to dismiss the opinions of older adults. Given the rise in usage of and the varied reactions to the phrase, it is important to understand how, "OK boomer, " was portrayed in print media. To do so, news articles from the New York Times ( NYT), Wall Street Journal ( WSJ ), and Washington Post ( WaPo ) that were printed during October 2019-February 2020 were collected. After organizing the data, a thematic analysis was completed, which showed that "OK boomer" was depicted as a form of demagogic discourse that reinforced age-based stereotypes. This portrayal relied on (1) an oversimplified definition of the phrase that was grounded in unidimensional stereotypes (2) the reinforcement of generational divides, and (3) the acceptance of ageist communicative behaviors in intergenerational interactions. Based on these findings, a series of theoretical and applied implications that problematize the use of the phrase and encourage productive intergenerational interactions are provided.